INVESTIGATING OF BLACK HOLE ATTACK IN WIRELESS SENSOR NETWORK - Syed Muhammed Nouman Qadir (Spectrum of Engineering Sciences, 2025)
As we enter the era of sensors different types of sensors are deployed everywhere for making different types of Networks such as MANET, WBAN, VANET, etc. All of these are the categories of wireless sensor networks and in all categories, the sensor is deployed to collect data and transmit it to the sensor head node or base stations during the data transmission a variety of security threats are available some of them are active and some of them are passive all active. In this paper we discussed various security attacks that directly affect the performance of a node or network (performance-oriented attack), creating the violence in layers (layer-oriented attack) and achieving some goals (goals-oriented attack) in detail also discussed the countermeasures for all types of attacks. This paper is specially designed for the investigation of black hole attacks in the WSNs network we also cover the detection of blackhole attacks and their prevention technique.